Relationship between Attachment Dimensions and Emotion Regulation among Adolescents - Khadeejah Iqbal (Journal of Management Practices, Humanities and Social Sciences, 2024)
Early experiences with attachment figures significantly influence the development of emotional regulation, which plays a crucial role during the transition from childhood to adolescence—a period marked by rapid psychological and physiological changes. This research aimed to explore the relationship between attachment dimensions and the regulation of three types of emotions—anger, sadness, and fear- among children and early adolescents aged 10-16. A cross-sectional study design was employed. The sample consisted of 312 students (140 males and 172 females) from government and private schools in Islamabad, with a mean age of 13.8 years (SD=1.57). The "Experiences in Close Relationships" (ECR) instrument, in age-appropriate versions, was used to assess the attachment dimensions of both children and their mothers. The children's emotion regulation strategies were assessed using the "Emotion Regulation Inventory" (ERI). Both instruments were translated into Urdu following World Health Organization (WHO) guidelines for translation of interventions. The most endorsed emotion among the sample was anger, while the least endorsed emotion was sadness. Alpha reliabilities for the instruments ranged from 0.65 to 0.85. Regression analysis revealed that attachment anxiety was positively associated with anger suppression and fear dysregulation. Attachment avoidance was associated with anger dysregulation and fear suppression. No significant association was found for the emotion of sadness. The results highlight the complex dynamics between attachment dimensions and emotion regulation. Children with attachment anxiety tend to suppress anger and dysregulate fear, whereas those with attachment avoidance tend to dysregulate anger and suppress fear. The study underscores the importance of considering attachment styles in understanding emotion regulation strategies in children and adolescents, as these dynamics have significant implications for daily life interactions and psychological development